THE EFFECT OF WORK PLACEMENT ON THE WORK MOTIVATION OF ALUMNI POLITEKNIK LP3I JAKARTA - Alya Hasan Basri; Serly Aluwanita; Siti Fatimah (POLITEKNIK LP3I JAKARTA, 2026)
This study examines whether job placement influences the work motivation of Politeknik LP3I Jakarta alumni, using a descriptive-correlational quantitative design. The population comprised Business Administration graduates (2021–2025 cohorts) with at least one year of work experience in Jabodetabek, from which 30 respondents were drawn via probability sampling. Data were collected using a Likert-scale questionnaire, which proved valid (r-count above the 0.3610 r-table value) and highly reliable (Cronbach's Alpha = 0.95), with normally distributed data and no multicollinearity or heteroscedasticity issues. Simple linear regression produced the equation Y = 60.866 + 0.133X. As the t-count (1.833) was below the t-table value (2.048) and the significance level (0.077) exceeded 0.05, job placement was found to have no significant effect on work motivation. The R² of 0.107 indicates job placement explains only 10.7% of motivation variance, with the remaining 89.3% attributable to factors such as compensation, working conditions, leadership, and career development suggesting other variables play a more dominant role and warrant further study.